Cooperation and Hegemony in US-Latin American Relations Revisiting the Western Hemisphere Idea - Scarfi, Juan Pablo; Tillman, Andrew R.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book reconsiders the so-called Western Hemisphere idea, showing that it can be conceived as an illuminating and flexible conceptual framework through which we can gain new and enriching insights into the history and politics of US-Latin American relations.
Keywords: Science; Science; Science, general; Electronic books